2017
DOI: 10.1186/s12913-017-2635-z
|View full text |Cite
|
Sign up to set email alerts
|

Trial and error: evaluating and refining a community model of HIV testing in Australia

Abstract: BackgroundThe 2012 regulatory approval of HIV rapid point of care (RPOC) tests in Australia and a national strategic focus on HIV testing provided a catalyst for implementation of non-clinical HIV testing service models. PRONTO! opened in 2013 as a two-year trial delivering peer-led community-based HIV RPOC tests targeting gay, bisexual and other men who have sex with men (GBM), with the aim of increasing HIV testing frequency. Initial data suggested this aim was not achieved and, as part of a broader service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…An Australian study on a non-clinical HIV service testing called, PRONTO! showed that end users seemed to prefer doctors or nurses when compared to lay providers [ 31 ]. This may indicate that lay providers’ involvement is accepted by clients, but does not have to be the decisive factor to choose for AHF-Checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study on a non-clinical HIV service testing called, PRONTO! showed that end users seemed to prefer doctors or nurses when compared to lay providers [ 31 ]. This may indicate that lay providers’ involvement is accepted by clients, but does not have to be the decisive factor to choose for AHF-Checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…at all due to the lack of STI testing, previous surveys of clients also indicated ongoing HIV testing at PRONTO! alongside intermittent HIV testing elsewhere 31 . Intermittent testing at PRONTO!…”
Section: Discussionmentioning
confidence: 99%
“…may have attenuated some of these barriers, we have previously shown that the absence of STI testing at the service created a barrier to returning, some clients reporting returning to testing for HIV at other services after their first test at PRONTO!. 31 The lack of STI testing at PRONTO! likely contributed to the difference in the proportion of GBM returning for a HIV test at PRONTO!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that while features of the HIV testing service model (e.g. community‐based, peer‐led, RPOC test) were highly acceptable , the lack of sexually transmissible infection (STI) testing introduced a significant barrier to returning to the service for HIV testing .…”
Section: Introductionmentioning
confidence: 99%